Kardiochirurgia dorosłychLeft ventricle function and natriuretic peptide concentrations in patients with aortic valve replacement for isolated aortic valve stenosis. One year follow-up - Reszka, Beata; Biernat, Jolanta; Roleder, Tomasz; Jasiński, Marek; Jakubowski, Daniel; Malinowski, Marcin; Dalecka, Anna-Maria; Twardowski, Romuald; Piotrowski, Witold; Deja, Marek; Woś, Stanisław; Gołba, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Replacement of the stenotic aortic valve leads to regression of the left ventricle mass and to improvement of left ventricle systolic and diastolic function. There are few data regarding the rate of reduction of plasma concentration of natriuretic peptides following aortic valve replacement. The aim of the study was to correlate the rate of left ventricle function improvement and reduction of plasma levels of natriuretic peptide type B (NT-proBNP) and atrial natriuretic peptide (NT-proBNP) in mid-term follow-up of aortic valve replacement in patients with severe aortic valve stenosis. Material and methods: 67 patients with isolated severe aortic valve stenosis were prospectively followed after aortic valve replacement. NT-proBNP and NT-proANP plasma levels were measured and left ventricle systolic and diastolic function indices were evaluated with echocardiography preoperatively and then 30 days and 6 and 12 months postoperatively. Results: The baseline high levels of NT-proBNP and NT-proANP decreased at 6 months and 30 days after replacement, respectively. NT-proBNP reduction best correlated with the left ventricle mass index (LVMi) regression. There was a relation between NT-proBNP level and left ventricle diastolic function indices. The left ventricle ejection fraction, LVMi and maximal velocity of the A wave are independent predictors of the preoperative plasma concentration of NT-proBNP. The left ventricle end-diastolic volume index, LVMi and left atrial volume are independent predictors of the preoperative plasma concentration of NT-proANP. Conclusion: The rates of reduction of NT-proBNP and NT-proANP plasma levels following aortic valve replacement in patients with severe aortic stenosis are not parallel and depend on different left ventricle function indices.